Electrochemical performance of polyaniline/ZnO composite and bilayer electrodes for high-power supercapacitors - Bulgurcuoglu, Ayse Evrim (INDERSCIENCE ENTERPRISES LTD, 2026)
This study investigates the electrochemical performance of polyaniline (PANI), zinc oxide (ZnO), and their bilayer and composite electrodes for supercapacitors. Cyclic voltammetry, galvanostatic charge-discharge, and Ragone plot analyses were used to evaluate energy and power characteristics. PANI exhibits high energy density but limited stability, while ZnO maintains performance at high power densities. The PANI/ZnO bilayer shows moderate improvement; however, the PANI/ZnO composite achieves the highest energy density of 6.39 Wh kg(-1) at 0.27 W kg(-1) and retains nearly 100% capacitance after 1,500 cycles, demonstrating superior stability and efficiency.
Keywords: polyaniline; PANI; zinc oxide; ZnO; bilayer; supercapacitor; Environmental Sciences & Ecology